Clinical features and response to treatment of prolactinomas in children and adolescents: a retrospective single-centre analysis and review of the literature - Breil, Thomas; Choukair, Daniela; Mittnacht, Janna; Inta, Ioana; Klose, Daniela; Jesser, Jessica; Bettendorf, Markus (Hormone research in paediatrics, 2018)
Background: Paediatric prolactinomas are rare. The aim of this study was to investigate the clinical features and outcome of paediatric patients with prolactinomas. Methods: In this single-centre retrospective analysis, clinical, biochemical, and radiological features of all paediatric patients with pituitary adenomas diagnosed between 2000 and 2016 were evaluated. Results: Among 21 patients with pituitary adenomas, 12 patients with prolactinomas (median age 14.2 years, range 11–16.6 years, 8 females, 4 males) were identified (7 macro- and 5 microprolactinomas). The most common clinical symptoms were headaches (67%) and pubertal delay (67%). All patients with macroprolactinomas with prolactin concentrations >10,000 mU/L had at least 1 pituitary hormone deficiency. Cabergoline as first-line treatment (n = 11, median follow-up of 37 months, range 12–89 months) induced normoprolactinemia (n = 8), reduced the mean tumour volume by 80%, and ameliorated headaches (p = 0.016) and pubertal delay (p = 0.031), whereas intermittent moderate side effects occurred in 55%. Conclusion: Adolescents with headaches and pubertal delay should be investigated for prolactinomas. Treatment with cabergoline is well tolerated and effective in reducing clinical symptoms and prolactin concentrations was well as inducing tumour shrinkage. Further clinical prospective studies are needed to standardize paediatric treatment modalities.
Gesehen am 15.08.2019